Mexico: Rights experts ‘outraged’ over attacks on women activists - UN News (UN News, 2023)
A group of UN independent human rights experts on Wednesday urged the Government of Mexico to investigate and prosecute those who attack and kill women activists searching for their missing relatives. |
Keywords: 2023-08 August